Effects of non-invasive spinal cord stimulation on autonomic function in individuals with subacute spinal cord injury: A pilot clinical trial protocol - Ryo Nakahara; Sarah Nasson; Ellie Bieler; Emilee Putsche-Young; Benjamin Aguila; Jiayi Shen; Emma Chung; Laura Winston; Stephen Burns; Deborah Crane; Margaret Eugenio; Klaus Krogh; et al. (PLoS ONE, 2026)
Introduction Spinal cord injury (SCI) at or above the thoracic sixth spinal cord level disrupts descending sympathetic and parasympathetic control, leading to severe autonomic dysfunctions including cardiovascular and pelvic organ function. These complications adversely affect the quality of life and are associated with increased morbidity and mortality after SCI. Transcutaneous spinal cord stimulation (tSCS) may offer therapeutic benefits for these functions. The safety of tSCS in subacute SCI, however, remains unknown. Therefore, this study aims to evaluate the feasibility of tSCS for autonomic recovery in individuals with subacute SCI within six months since injury. Methods and analysis We designed a two-phase clinical protocol consisting of a pilot randomized controlled trial conducted during inpatient rehabilitation (Project A), followed by a post-discharge outpatient phase with a single-arm quasi-experimental design (Project B). In Project A, 26 adults with cervical or upper thoracic (≥T6) American Spinal Injury Association Impairment Scale (AIS) A-C SCI are planned to be enrolled and randomly assigned to receive tSCS or sham stimulation for five sessions (up to 90 minutes each) in parallel with standard care. Following discharge from inpatient rehabilitation, eligible participants will be offered continuation in Project B. New eligible participants who have not participated in Project A will also be recruited into Project B. They will receive 18 tSCS sessions over six weeks in the laboratory setting. Primary outcomes focus on feasibility, including recruitment, retention, and stimulation-related adverse events. Clinical outcomes will be collected at baseline, after each intervention, and at six months and one-year post-injury. Feasibility results will be summarized descriptively, and exploratory analyses of autonomic outcomes, including cardiovascular and pelvic organ function, will provide preliminary estimates of autonomic responses. Ethics and dissemination The study has been approved by the University of Washington Institutional Review Board. Written informed consent will be obtained from all participants. Results will be submitted to peer-reviewed journals and shared with the scientific/clinical communities and individuals with lived experience of SCI. Trial registration ClinicalTrials.gov NCT06540859